Gallbladder Tuberculosis Mimicking Gallbladder Carcinoma: A Case Report and Literature Review - Yao Liu; Kai Wang; Heng Liu (Case Reports in Hepatology)
Gallbladder tuberculosis (GT) is extremely rare, and it is difficult to differentiate from other gallbladder diseases, such as gallbladder carcinoma and Xanthogranulomatous Cholecystitis. A correct preoperative diagnosis of GT is difficult. The final diagnosis is usually made postoperatively according to surgical biopsy. Here, we report a case of a patient who underwent surgery with the preoperative diagnosis of gallbladder carcinoma. We reviewed the literature and present the process of differential diagnosis between two or more conditions that share similar signs or symptoms.